Effect of Silver Content on the Wear and Mechanical Properties of Powder Metallurgical Ti-5Al-2.5Fe-xAg Alloys - YAMANOGLU, RIDVAN; Khoshnaw, Fuad; Daoud, Ismail; Efendi, Erdinc (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
In the current research, the effect of Ag on the mechanical properties of Ti5Al2.5Fe alloy has been investigated. The Ti5Al2.5Fe alloy, with different amounts of Ag ranged from 1 to 5% wt. was prepared by mechanical mixing and then fabricated by hot pressing at 950 oC for 15 min under 50 MPa. Three holding steps were applied to the powder compacts to restrain the liquid phases inside graphite die before reaching the maximum sintering temperature. The sintered samples were subjected to hardness, bending and wear tests to study the effect Ag on the mechanical properties of Ti5Al2.5Fe alloy. The microstructural characterization was carried out by means of optical and scanning electron microscope. The results showed that Ag played a differential role on the mechanical properties supported by microstructural constituents. The bending strength and hardness of the produced samples increased with the addition of Ag, the hardness of the alloys then tends to decreased with increasing Ag content but still remained above the hardness of Ti5Al2.5Fe alloy. Wear test also showed similar trends with hardness test results. Finally, the optimum Ag content for the Ti5Al2.5Fe alloy has been determined as wt.1%. XRD tests showed that unsolved Ag content was the main reason for the decrease in the mechanical properties.